ALS-Linked SOD1 Mutants Enhance Neurite Outgrowth and Branching in Adult Motor Neurons - Osking, Zachary; Ayers, Jacob I.; Hildebrandt, Ryan; Skruber, Kristen; Brown, Hilda; Ryu, Daniel; Eukovich, Amanda R.; Golde, Todd E.; Borchelt, David R.; Read, Tracy-Ann; Vitriol, Eric A. (iScience, 2019)
Amyotrophic lateral sclerosis (ALS) is a progressive, fatal neurodegenerative disease characterized by motor neuron cell death. However, not all motor neurons are equally susceptible. Most of what we know about the surviving motor neurons comes from gene expression profiling; less is known about their functional traits. We found that resistant motor neurons cultured from SOD1 ALS mouse models have enhanced axonal outgrowth and dendritic branching. They also have an increase in the number and size of actin-based structures like growth cones and filopodia. These phenotypes occur in cells cultured from presymptomatic mice and mutant SOD1 models that do not develop ALS but not in embryonic motor neurons. Enhanced outgrowth and upregulation of filopodia can be induced in wild-type adult cells by expressing mutant SOD1. These results demonstrate that mutant SOD1 can enhance the regenerative capability of ALS-resistant motor neurons. Capitalizing on this mechanism could lead to new therapeutic strategies. [Display omitted] •Motor neurons from end-stage SOD1 ALS mice have enhanced neurite outgrowth/branching•Increased outgrowth in adult neurons is independent of ALS symptoms•SOD1G93A adult motor neurons have larger growth cones and more axonal filopodia•Acute SOD1G93A expression upregulates outgrowth in wild-type adult motor neurons Biological Sciences; Genetics; Neuroscience; Cell Biology